Persepsi Siswa Terhadap Proses Pembelajaran Yang Dilakukan Oleh Guru Bidang Studi Ekonomi Di SMA Negeri 3 Banda Aceh - Rahmawati Rahmawati; Ruaida Ruaida; Amiruddin Amiruddin (Universitas Syiah Kuala, 2019)
This study raised the question of how students' perceptions of their lessons teachers of economics at SMA Negeri 3 Banda Aceh. This study aims to determine students' perceptions of three stages of the learning process, namely: opening activities, the core, and the closing of learning. Respondents in this study were students in social studies classes 1, 2, and 3 totaling 50 students. The approach taken in this study is a quantitative approach with descriptive research. The data collection is done with the initial observation and questionnaires / kousioner. Data were analyzed by using the formula percentage (%) and average ((X) ). The results showed that although the students' perception of the process undertaken economic studies teachers in SMA Negeri 3 Banda Aceh at the stage of open learning activities categorized either with an average score of 2.97 on a stage core activities are categorized either with an average score of 3.11 and on closing the learning taham categorized both by a score average score of 3.06.